GAMBARAN PENGETAHUAN WANITA USIA SUBUR (WUS) TENTANG KONTRASEPSI IUD DI WILAYAH KERJA PUSKESMAS DANUREJAN 1 KOTA YOGYAKARTA - Rahmawati, Dechoni; Solikhah, Siti (MEDIA ILMU KESEHATAN, 2017)
Background: The high birth rate in Indonesian is one of the major problems and requires special attention, the population increased in 2015 amounted to 255, 461, 686 people, the population in Indonesian is fourth after China, India, and Unite States (Depkes Indonesian, 2015). Data from the health service DIY, acceptors of IUD is the the lowest number in Yogyakarta , located in community health service Danurejan I as many as 215 acceptor Objectives: The aim of this study is to know the knowledge of women fertile about contraception in community health center Danurejan 1 Yogyakarta. Methods: Research design used was a descriptive quantitative research. The sampling technique used purposive sampling with the total of responden as many as 73. Data analysis used analysis univariat. Result: the result of this research shows that based on level knowledge WUS about contraception of IUD be categorized the level of knowledge as good is 50 responden (68.5%). In the category of enough of knowledge was 21 respondents ( 28.8%) and lack of knowledge as lack is 2 respondents (2.7%). Conclusion: Based on the result of this research which had done showed that WUS knowledge about IUD contraception in community health center Danurejan 1 Yogyakarta mostly of responden having good knowledge as many as 50 responden (68.5%) Keywords: Knowledge, Women Fertile (WUS), IUD Contraception